On the need for an international lender of last resort: Lessons from domestic financial markets - Adalbert Winkler (University of Würzburg, Department of Economics, 2001)
The increasing incidence and intensity of crises in the international financial markets during the 1990s have given new impetus to the debate on reform of the international financial system. Much of the discussion focuses on the idea of an international lender of last resort which could provide liquidity to ensure the stability of the international financial system. This paper responds to the question of whether an international lender of last resort is necessary by presenting both the differences and the similarities between a domestic financial market and an international one. This comparison will show that in regard to those aspects which justify the existence of a lender of last resort at the national level, the two types of financial markets are no different: If commercial banks are engaging in maturity and liquidity transformation, then the existence of a lender of last resort is a prerequisite to stable and crisis-free development of financial markets. Both the recent financial crises, and the developments which can be observed in the banking sectors of Latin America and Eastern Europe, provide empirical evidence for this thesis. In these regions, banking sectors are emerging which are increasingly dominated by foreign banks, and thus have indirect access to an international lender of last resort. At the same time, there is an increasing tendency within emerging markets to introduce regulations which limit the extent to which transformation is performed in financial markets, and thus to limit as far as possible the risks which make an international lender of last resort necessary.
Keywords: E42; E44; F33; G21; 330; lender of last resort; maturity transformation; liquidity transformation; financial crisis; currency crisis